Analysis of Transformational Leadership in the Strategy for Developing Civil Servant Competence in National Institute of Public Administration - Alisya Dwi Purwanti; Laode Rudita (Golden Ratio of Human Resource Management, 2026)
The leadership crisis amidst demands for transformational leadership in developing the competencies of state civil servants (ASN) presents a strategic challenge to fostering high-quality human resources in pursuit of Golden Indonesia 2045. This study aims to analyze the role of transformational leadership in addressing the transformation of civil servant competency development and formulating relevant strategies. This study uses a qualitative approach through a literature review, examining secondary data such as government regulations, official reports, and academic articles from 2020 to 2026 related to ASN leadership and competency development, analyzed using descriptive-qualitative analysis and thematic synthesis based on elements of transformational leadership. The results show that transformational leadership plays a significant role in driving organizational change through charismatic, inspirational, and adaptive traits, and that civil servant competency development is a strategic imperative that must be integrated with organizational goals. In addition, there are various challenges, such as the digital divide, resistance to change, low learning motivation, and lack of integration of learning systems. Therefore, effective strategies include developing an ASN learning ecosystem, implementing an ASN Corporate University, and strengthening the role of BPSDM as a driver of talent development and a knowledge center. This analysis demonstrates that civil servant competency is a key catalyst for sustainable bureaucratic reform. To foster a truly agile, adaptive, innovative, and results-oriented apparatus, the government must treat competency development not as an isolated administrative routine, but as an integrated, mandatory, and strategic investment. Transformational leadership strategies act as a key driver for dismantling institutional silos and accelerating bureaucratic reform. Therefore, learning organizations require a learning ecosystem and a civil service corporate university (ASN Corpu).